Racial disparities in hospitalization expenditures of older adults in Singapore. (17th December 2021) - Chen, Cynthia; Guo, Xueying; Wee, Hwee Lin; Tan, Kelvin Bryan
Abstract: The World Population Prospects 2019 reports that the proportion of people who aged 65 and above takes up 9 per cent globally in 2019, reaching up to 16 per cent by 2050. Asia has the fastest rise: from 1 in 9 people aged 65 and above to 1 in 4 in 2050. Rapid growth in older adults has strong implications for diseases and healthcare expenditure. For Singapore, the transition from 'ageing society' (7% seniors) in 1999 to 'super-aged society' (20% seniors) in 2026 is projected to take 27 years, much faster than Japan's 36 years. We used the Singapore Multi-Ethnic Cohort (MEC) of 14, 465 subjects aged 21 to 94, and the Future Elderly Model (FEM) microsimulation model to project disease burden and hospitalization expenditures to 2050. We found that Chinese females had the highest life expectancy of 86.0 years, followed by Indian and Malay females with 80.4 and 75.6 years respectively. In all racial groups, women lived longer than men by 5-7 years. Cumulative hospitalization expenditures of older adults aged 51+ was US$69, 500 for Chinese, US$67, 600 for Malays and US$86, 100 for Indians; US$71, 200 for males and US$70, 700 for females. The increased hospitalization spending for all three ethnic groups was due to the underlying manifestation of chronic diseases, including diabetes, hypertension, heart disease and stroke. Variations in environmental risk factors such as diet, cigarette smoking and physical activity across ethnic groups may contribute to racial differences in chronic diseases and disability. Therefore, targeted interventions are needed to reduce racial disparities.